The potential of utilising papaya seed oil and stone fruit kernel oil as non-edible feedstock for biodiesel production in Australia—A review. (November 2019) - Anwar, Mohammad; Rasul, Mohammad G.; Ashwath, Nanjappa; Nabi, MD. Nurun
Abstract: This paper reviews and discusses the potential of papaya seed and stone fruit kernel biodiesels — the two sources of 2nd generation transport biodiesels in Australia. The challenges associated with biodiesel production and their possible solutions, particularly on feedstock selection, oil extraction, conversion of oil into biodiesel, biodiesel storage and transport, costs of production and the information needs for commercialising these sources of biodiesels are discussed, along with the eco-friendly attributes of these biodiesels to Australian transport sector. Some researchers report that the use of papaya seed and stone fruit kernel biodiesels reduce engine power only 2 to 5%), however significantly reduce harmful engine emission such as HC reductions of 9 to 19%, PM reductions of 19.5 to 35% and CO reductions of 11 to 29%.